Bibliometric Analysis and Systematic Review of Social Media‎Marketing Research Trends, Identifying Thematic Clusters and ‎Emerging Trends - Das, Tilak Ch; Shandilya, Saptadweepa; Barman , Manyata (International Journal of Accounting and Economics Studies, 2025)
The rapid growth of social media has significantly influenced marketing practices, making it a ‎central topic of academic interest. This paper offers a comprehensive review of research in social ‎media marketing (SMM) from 2010 to 2024. A total of 98 peer-reviewed articles were analyzed ‎using a dual-method approach—systematic review, following PRISMA guidelines, and ‎bibliometric mapping through VOSviewer software. The analysis highlights a clear increase in ‎research output after 2015, reflecting the growing role of social platforms in marketing strategy. ‎Four major themes are identified: consumer engagement, brand strategy development, platform-specific marketing approaches, and ethical considerations such as data privacy and algorithmic ‎fairness. The review also reveals a shift toward more rigorous methodologies, with increased use of ‎mixed methods and longitudinal studies. Geographical analysis shows a research concentration in ‎North America and Europe, with limited contributions from emerging markets. By synthesizing ‎past findings and identifying gaps, this study provides direction for future research and practical ‎insights for marketers navigating an evolving digital landscape. It adds value by clarifying the ‎structure of the field, highlighting key influencers, and suggesting areas where further investigation ‎is both possible and needed‎.